Utilization of House Plants for Tanned Leather Ecoprint Coloring in Sumbersekar Village - wehandaka pancapalaga; S. Suyatno (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Sumber Sekar Village is one of the villages that has a lot of flower plants, therefore it is called Sumber Sekar. The leaves and flowers in Sumber Sekar Village have not been used optimally. The various types of leaves and flowers contain pigments that can still be used as ecoprint coloring on tanned skin. The ecoprinting leather products produced can be used in the production of garments, shoes and jackets, especially for fashion. The purpose of this community service is to increase the knowledge and skills of the people in Sumbersekar Village in using leaves and flowers as ecoprinting coloring on leather. This service was carried out in July 2020 with 20 participants. Service methods used in education, training and mentoring. Education is given to increase knowledge of ecoprinting on leather. Training was given to improve skills in making the ecoprinting method of coloring on leather. Meanwhile, assistance for those who are interested in business. Community service evaluation is carried out by comparing the increase in the percentage of knowledge and skills before and after the training. Community Service Results In general, the training went well. The knowledge level of the participants increased by 59% and the skills of the participants increased by 57%. The conclusion is that the training program that has been carried out is able to improve the knowledge and skills of participants in the use of leaves and flowers around the house to be used as natural coloring using the ecoprint method on leather.